Caste in itself, caste and class, or caste in class - Mukherjee, Ramkrishna (1999)
The debate surrounding the relationship between caste and class is discussed here in the context of historical and contemporary perspectives in India, maintaining that what exists in India is caste in class, not caste per se or caste and class. - Reproduced
Keywords: Caste